2002
DOI: 10.1139/z02-186
|View full text |Cite
|
Sign up to set email alerts
|

The influence of resource seasonality on the breeding patterns of the Eurasian otter (Lutra lutra) in Mediterranean habitats

Abstract: Litters of small Eurasian otter (Lutra lutra) cubs ranged from one to four, with those of one and two accounting for 95%. Significant variations were found between locations and according to the main diet (average ranging between 1.1 and 2.4 cubs/female). We found a seasonal pattern in otter breeding in some areas, being different in each. In the Prepyrenees, most births took place between March and June (85%). In Mediterranean rivers of the Ebro basin, most births occurred between December and February (57%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 20 publications
1
28
0
7
Order By: Relevance
“…For example, by reducing aquatic plant biomass, crayfish reduce the availability of refuges to macro-invertebrates and fish, which may indirectly benefit higher trophic levels (such as predatory fish, birds and otters) by increasing prey vulnerability. Despite evidence suggesting that predation on crayfish increased juvenile otter survival (Ruiz-Olmo et al 2002) and that invasive red swamp crayfish were readily preyed upon by four species of mammalian carnivores and five species of ciconiiform birds (Correia 2001), there are currently too few data to properly assess the importance of crayfish as a dietary component for such predators. Our literature review did, however, suggest that crayfish can drive top-down trophic cascades.…”
Section: Discussionmentioning
confidence: 99%
“…For example, by reducing aquatic plant biomass, crayfish reduce the availability of refuges to macro-invertebrates and fish, which may indirectly benefit higher trophic levels (such as predatory fish, birds and otters) by increasing prey vulnerability. Despite evidence suggesting that predation on crayfish increased juvenile otter survival (Ruiz-Olmo et al 2002) and that invasive red swamp crayfish were readily preyed upon by four species of mammalian carnivores and five species of ciconiiform birds (Correia 2001), there are currently too few data to properly assess the importance of crayfish as a dietary component for such predators. Our literature review did, however, suggest that crayfish can drive top-down trophic cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has led to a better inventory and understanding of biotic assemblages in NPRS, including aquatic (Graça et al, 2004;Datry, 2012;Bonada and Resh, 2013;García-Roger et al, 2013) and terrestrial invertebrates Datry, 2012, 2015;, diatoms (Novais et al, 2014;Barthès et al, 2014), microbial and algal assemblages (Amalfitano et al, 2008;Romani et al, 2013) as well as vertebrate assemblages, such as fish (Pires et al, 1999;Zogaris et al, 2012;Vardakas et al, 2015) and semi-aquatic carnivores (Clavero et al, 2003;Ruiz-Olmo et al, 2002. Other recent studies focused on the mechanisms allowing species to cope with recurrent drying as well as to produce quantitative relationships between drying duration and frequency (Datry et al, 2014b).…”
Section: Biotic Responses To Flow Intermittencymentioning
confidence: 99%
“…Consequently, the mortality rate of otters increases, their abundance diminishes, and breeding success declines (e.g., Ruiz-Olmo et al, 2001). Furthermore, due to summer droughts, the breeding time of otters occurs earlier in Mediterranean than in temperate streams (Ruiz-Olmo et al, 2002).…”
Section: Biotic Responses To Flow Intermittencymentioning
confidence: 99%
“…We noted if reproductive events had been produced in each of the studied years, and classified them in the classes 0%, 1-20%, 2-40%, 41-60%, 61-80%, or 80-100%, assigning them a value of 0, 1, 2, 3, 4, or 5 for the statistical analysis, respectively. In 46 cases, the breeding frequency was determined from studies from 1984 to 2006 (Ruiz-Olmo et al 2002, 2005a.…”
Section: Sampling Designmentioning
confidence: 99%
“…Otters adapt their breeding to occur when abundance of such species in the environment is maximal (Kruuk et al 1987;Heggberget 1993;Beja 1996;Elmeros and Madsen 1999;Ruiz-Olmo et al 2002, 2003. Ruiz-Olmo et al (2001, 2003 found a positive correlation between otter breeding success and both the abundance of food and the number of main fish species consumed.…”
Section: Introductionmentioning
confidence: 99%